Modeling and homogenization of processes in cylindrical layered composites like capacitors and transformers - Сандраков, Геннадій; Киричек, Микола (Київський національний університет імені Тараса Шевченка, 2025)
Capacitors and transformers are widely used devices. There is a trend towards minutearization of such devices. Thus, a natural problem of modeling thermal and electromagnetic processes in such devices arises. Understanding the models of such processes allows, for example, to optimize or make cheaper of these devices. But, the geometry of such devices is very specific. For example, a regular capacitor is a long strip with an insulator rolled into a cylinder. Direct modeling of processes in such a device is complicated, since there are very many layers, which leads to equations with highly oscillating coefficients. On the other hand, methods of homogenization theory can be applied to such equations and equations with constant coefficients can be obtained, the solutions of which approximate the solutions of the equations under consideration. The solution of equations with constant coefficients is much simpler both by numerical and analytical methods. As a first step in this direction, one dynamic equation will be considered here, which corresponds to the modeling of wave and thermal processes. Thus, the problem of modeling wave and thermal processes in a cylinder consisting of a large number of alternating layers with different characteristics is considered. Using the asymptotic methods of the homogenization theory, this problem is approximately reduced to modeling processes in a homogeneous (homogenized) cylinder. Asymptotic expansions and homogenized problems are presented, the solutions of which determine the approximate asymptotic of solutions to the problem under consideration. Formulas for calculating the characteristics of the homogeneous cylinder and accuracy estimates of the approximations are given. The presented accuracy estimates of such approximations are essential for numerical calculations and computer modeling of the problems with guaranteed accuracy. In addition, the given approximations are undoubtedly useful for understanding wave and thermal processes in devices similar to capacitors and transformers. This approach can be considered as a basis for considering more general electromagnetic and thermal processes, which are modeled by Maxwell's equations coupled with the heat equation. Pages of the article in the issue: 71 - 82 Language of the article: English

Конденсатори та трансформатори є допоміжними пристроями, які широко використовуються в сучасному житті. Нині спостерігається тенденція до мініатюризації таких пристроїв. Отже, виникає природна проблема моделювання теплових і електромагнітних процесів у них. Розуміння моделей зазначених процесів дає змогу, наприклад, оптимізувати або здешевити такі пристрої. Проте геометрія таких пристроїв дуже специфічна. Звичайний конденсатор, наприклад, являє собою згорнуту в циліндр довгу стрічку, укриту ізолятором. Безпосереднє моделювання процесів у такому пристрої складне, оскільки існує дуже багато шарів, що призводить до рівнянь зі швидко осцилюючими коефіцієнтами. З іншого боку, до таких рівнянь можна застосувати методи теорії гомогенізації й отримати рівняння зі сталими коефіцієнтами, розв'язки яких апроксимують розв'язки рівнянь, які розглядаємо. Зрозуміло, що значно простіше розв'язувати рівняння зі сталими коефіцієнтами як чисельними, так й аналітичними методами. Як перший крок у цьому напрямі, у пропонованому дослідженні розглянуто задачу моделювання хвильових і теплових процесів у циліндрі, що складається з великої кількості шарів з різними характеристиками, які чергуються. За допомогою асимптотичних методів теорії гомогенізації цю задачу наближено зведено до моделювання процесів в однорідному (гомогенізованому) циліндрі. Наведено асимптотичні розклади та гомогенізовані задачі, розв'язки яких визначають наближену асимптотику розв'язків задачі, яку ми розглядаємо. Наведено формули для розрахунку характеристик однорідного циліндра й оцінки точності наближень. Подано також оцінки точності цих апроксимацій, що необхідні для чисельних розрахунків і комп'ютерного моделювання таких проблем з гарантованою точністю. Крім того, наведені наближення, безсумнівно, корисні для розуміння хвильових і теплових процесів у пристроях, подібних до конденсаторів і трансформаторів. Зазначений підхід можна розглядати як основу для моделювання загальніших електромагнітних і теплових процесів, що моделюються рівняннями Максвелла в поєднанні з рівнянням теплопровідності.
Моделювання і гомогенізація процесів у циліндричних шаруватих композитах, таких як конденсатори та трансформатори
Keywords: initial boundary value problems; homogenized problems; wave equations; heat equations; asymptotic expansions; heat conductivity coefficients; wave propagation speed coefficients; початково-крайові задачі; гомогенізовані задачі; хвильові рівняння; рівняння теплопровідності; асимптотичні розвинення; коефіцієнти теплопровідності; коефіцієнти швидкості поширення хвиль